2008
DOI: 10.2113/jeeg13.1.13
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Magnetic Susceptibility and Heavy Metal Concentrations in Forest Soils of the Eastern Czech Republic

Abstract: Magnetic susceptibility measurements were performed on 2,000 samples of forest soils from the Ostrava-Karvina industrial region (Czech part of Upper Silesian Coal Basin) and the Moravian-Silesian Beskydy Mountains and their piedmont area, Podbeskydi. Concentrations of selected elements were determined in 1,200 samples from the same set. Industrial facilities (metallurgical industry and power plants) located in this region represent major sources of both magnetic particles and risk elements contaminating soils … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…Many previous studies have suggested that pollutant inputs, especially heavy metal pollution, usually accompany enhanced magnetism in the topsoil in urban and industrial areas (Gautam et al, 2004;Wang and Qin, 2005;Blaha et al, 2008;Matysek et al, 2008). In order to study the relation between soil magnetic properties and anthropogenic emission, the industrial density for each administrative district, which was calculated as gross industrial output value (in unit of million RMB Yuan, from 2001 to 2010) normalized by corresponding area (Statistics Bureau of Guangdong Province, Guangdong Survey Office of National Bureau of Statistics, 2002Statistics, -2011, is illustrated in Fig.…”
Section: Relation Between Magnetic Properties and Metal Elements In Amentioning
confidence: 99%
“…Many previous studies have suggested that pollutant inputs, especially heavy metal pollution, usually accompany enhanced magnetism in the topsoil in urban and industrial areas (Gautam et al, 2004;Wang and Qin, 2005;Blaha et al, 2008;Matysek et al, 2008). In order to study the relation between soil magnetic properties and anthropogenic emission, the industrial density for each administrative district, which was calculated as gross industrial output value (in unit of million RMB Yuan, from 2001 to 2010) normalized by corresponding area (Statistics Bureau of Guangdong Province, Guangdong Survey Office of National Bureau of Statistics, 2002Statistics, -2011, is illustrated in Fig.…”
Section: Relation Between Magnetic Properties and Metal Elements In Amentioning
confidence: 99%
“…The second mentioned park, Sad J. Jabůrkové, is situated in urban neighbourhood of old steelworks agglomeration. Significant quantities of Pb, As, Cd, Zn, and Fe were detected in industrial emissions in the area (Matýsek et al 2008). In the case of Sad J. Jabůrkové, the highest concentrations were found in the 10-20 cm depth, with a decrease to the top layer.…”
Section: Risk Elementsmentioning
confidence: 99%
“…the measure of magnetic susceptibility) are valuable aids in the detection and delimitation of areas affected by pollution (e.g. Lu et al, 2008;Matýsek et al, 2008;Sant' Ovaia et al, 2012;Strzyszcz and Ferdyn, 2005;Xia et al, 2011;Zhang et al, 2012). Therefore, they can be very useful when targeting and selecting sampling sites for subsequent geochemical analyses.…”
Section: Introductionmentioning
confidence: 99%